Aid for trade : a Caribbean perspective : a study - Parsan, Elizabeth (Caribbean Regional Negotiating Machinery Christ ChurchBB, 2006)
Presents an analytical overview of the key issues involved in the WTO Aid for Trade Initiative. Oulines the key components of an AFT package for the Caribbean, drawing upon the results of case studies involving Dominica, Dominican Republic, Jamaica and Guyana